Analysis of Barriers and Strategies to Enhance Community Participation in Utilizing Centralized Domestic Wastewater Treatment Systems in Jambi City, Indonesia - Putra, Dicky Nurfandi; Fitriani, Heni; Hadinata, Febrian (Fakultas Teknik Universitas Tanjungpura, 2025)
The development of Centralized Wastewater Treatment Plants (WWTPs) in Indonesia often faces negative public responses, leading to low community willingness to connect to the system. Through the Metropolitan Sanitation Management Investment Project (MSMIP), the government has initiated construction of WWTPs in several regions, including Jambi City, to address domestic wastewater issues. This study applies a mixed-methods approach to assess existing sanitation conditions and identify key factors inhibiting public participation across technical, economic, cognitive, perceptual, and institutional dimensions, analyzed using the Relative Importance Index (RII). Results show that 68.9% of households discharge wastewater without prior treatment, and 3.9% release both toilet and non-toilet waste directly into rivers. The community’s Average Ability to Pay (ATP) is IDR 103,000/month, considerably higher than the tariff of IDR 22,500/month, indicating that affordability is not a primary constraint. Instead, the main inhibiting factors include concerns about damage to the building during household connection installation, perceived increases in monthly maintenance costs, and the absence of clear local regulations. Limited public knowledge, assumptions that wastewater management is a government responsibility, and negative perceptions during construction further reduce willingness to participate. The study recommends strengthening regulatory frameworks, ensuring maintenance cost coverage, providing subsidies for low-income households, and enhancing outreach through collaboration with local academic institutions and community self-help groups.